2018
DOI: 10.1086/699522
|View full text |Cite
|
Sign up to set email alerts
|

Melanin-Based Skin Coloration Predicts Antioxidant Capacity in the Brown Trout (Salmo trutta)

Abstract: In many vertebrate species, individuals exhibit large variation in the degree of melanin-based coloration on their body. Dark and pale individuals differ in diverse physiological and behavioral traits, suggesting that melanic coloration may reveal individual quality. However, research into the relationships between physiological and skin traits, in terms of melanin-based skin coloration, in wild fish is scant. Our correlative study aimed at investigating the relationships between physiology and melanin-based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…If one wishes to measure aspects of coloration subject to phenotypic plasticity (Sköld et al ., ), our study suggests that confinement without anaesthesia is preferable, as has been noted by Parolini et al . (). If anaesthetics are to be used, MS‐222 may be preferable to clove oil given that sedation took slightly longer with clove oil, at the concentrations we employed (Bolasina et al ., for similar results with another poeciliid).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…If one wishes to measure aspects of coloration subject to phenotypic plasticity (Sköld et al ., ), our study suggests that confinement without anaesthesia is preferable, as has been noted by Parolini et al . (). If anaesthetics are to be used, MS‐222 may be preferable to clove oil given that sedation took slightly longer with clove oil, at the concentrations we employed (Bolasina et al ., for similar results with another poeciliid).…”
Section: Discussionmentioning
confidence: 97%
“…However, quantification of coloration traits in live poeciliids can pose challenges because the fish are so small. Colour measurement techniques involve using either reflectance spectrophotometry to, for example, address perceptual abilities, or to quantify the effects of pigment content on coloration (Grether et al ., ), or software‐based measurements taken from digital images, which are more suitable for examining patterns without necessarily obtaining absolute values of traits (Langkilde & Boronow, ; Maan et al ., ; McNeil et al ., ; Parolini et al ., ; Pike, ; Stevens et al ., ). Researchers wishing to measure coloration with minimal stress to the animal, for example because they will perform subsequent behavioral observations, often elect to use digital images (Bergman & Beehner, ; Foo et al ., ; Pike, ; Stevens et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased MMC associated with histopathological changes is related to oxidative stress leading to aggregation of immune cells [ 32 ]. In addition, the presence in melanomacrophages of lipofuscin or melanin, natural pigments with an antioxidant function like polyphenols and flavonoids [ 92 , 93 , 94 , 95 , 96 ], shows high involvement in the immune response [ 102 ]. A study by Giari et al (2008) showed that RCs increased significantly in number and size in kidney tubules of European sea bass exposed to high concentrations of mercury.…”
Section: Discussionmentioning
confidence: 99%
“…In salmonids, pigmentation and colour are also known to interact with social hierarchies, to influence mate choice and affect fitness (e.g. O’Connor, Metcalfe, & Taylor, 2000; Wedekind, Jacob, Evanno, Nusslé, & Müller, 2008; Marie-Orléach et al, 2014; Watt, Swanson, Miller, Chen, & May, 2017, Parolini, Iacobuzio, Bassano, Penatti, & Saino, 2018; Auld, Noakes, & Banks, 2019). However, if the physiological basis of colour changes are known (Leclercq, Taylor, & Migaud, 2010), the genomic basis of their pigmentation patterns remains largely unexplored, with only limited insights coming from quantitative trait loci (QTL) (Boulding et al, 2008) or few gene expression studies (Sivka, Snoj, Palandačic, & Sušnik Bajec, 2013; Djurdjevič, Furmanek, Miyazawa, & Sušnik Bajec, 2019).…”
Section: Introductionmentioning
confidence: 99%